The rights and obligations of states in disputed maritime areas - Logchem, Youri van (Cambridge : Cambridge University Press, 2021)
Many disputed maritime areas exist around the world. Often, the States concerned have not been able to reach agreement on how to, for example, regulate commercial activities within such areas. Conflict regularly arises between claimant coastal States if one of them acts unilaterally, such as in the South China Sea. This book examines the rights and obligations States have under international law concerning disputed maritime areas, in the first comprehensive treatment of this highly topical and pressing issue. It analyses conventional law, general international law, judicial decisions, State practice, and academic opinions that shine a light on the international legal framework that is applicable in disputed maritime areas. Proposing practical solutions on how to interpret the relevant international law, the book discusses the extent to which it currently provides clear guidance to States, and how international courts and tribunals have dealt with cases related to activities in disputed maritime areas.
Disputed maritime areas : setting the scene -- Disputed maritime areas : general rules of international law -- Disputed territorial sea and contiguous zone areas : applicable conventional rules -- Disputed EEZ and continental shelf areas : applicable conventional rules -- Case law involving the rights and obligations of states in disputed maritime areas -- Disputed maritime areas generated by claims made from disputed land territory : what are the rights and obligations of states? -- Acts of unilateralism in disputed maritime areas : a survey of state practice -- Are the rights and obligations of states in disputed maritime areas sufficiently defined in international law?
Title from publisher's bibliographic system (viewed on 04 Oct 2021).
Keywords: Maritime boundaries; Continental shelf -- Law and legislation; Contiguous zones (Law of the sea); Territorial waters; Jurisdiction, Territorial; Boundary disputes